Uma Análise da Proposta Pedagógica da Avaliação da Aprendizagem no Contexto dos Ciclos de Formação de Rede Municipal de Educação de Goiânia de 1998 a 2010 - SILVA, Marcos (2011)
The main subject of this dissertation is assessment in Educational Cycles in Goiânia‟s Municipal School System. The investigation was directed basically for these questions: how school managers and teachers understand the Cycles of evolution´s proposal and the assessment of learning? What are the characteristics of the assessment proposal for Goiânia‟s Municipal School System? What are the difficulties and improvements identified by teachers on the assessment proposal in the cycles of evolution context? On the way to get answers for those questions, could raise the research´s object based on this terms: identify the understanding of Scholl managers and teachers about Educational Cycles and assessment of learning. The main objective of this research was understand the Educational Cycles assessment of learning proposal in the Goiania´s municipal school system and their pedagogical aspects in the school managers and teachers point of view from 1998 to 2010. The methodology was based on a qualitative approach, as a case study, that investigated the assessment in the context of the Educational Cycles. To conduct the research was used as tool for data collection semi-structured interviews with School managers and teacher from Goiania‟s Municipal School System and document analysis of guidelines and educational policy proposals of the period covered. The theoretical foundations relied mainly on conceptions of assessment from: Cabrera, Chaves, Hoffmann, Rosales, Luckesi, Dalben, Tiballi among others. The research shows that there is an agreement between both school managers and teacher‟s point of view and the curriculum guidelines of Goiania‟s Municipal School System. It was possible identify the mainly difficulties and improvements on the evaluation‟s process in this education system. One of the factors added to this reality, was the fact that teachers did not participate in the implementation process of Educational Cycles, which caused and still causes a lot of resistance to the proposal especially in aspects related to assessment.